2010
DOI: 10.1007/s00417-009-1293-1
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond lenticule extraction for the correction of myopia: preliminary 6-month results

Abstract: FLEx appears to be a safe and promising corneal refractive procedure for correcting myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 19 publications
8
104
2
10
Order By: Relevance
“…9 Few studies are available to validate the outcome of the procedure, which has obtained CE Mark approval in 2009 but yet to be approved by the United States Food and Drug Administration. [7][8][9][10] Initial clinical results have been promising, where postoperative refractive outcomes were comparable to standard LASIK with few complications. 11,12 However, more studies are needed to assess the safety and efficacy of this new surgical procedure.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…9 Few studies are available to validate the outcome of the procedure, which has obtained CE Mark approval in 2009 but yet to be approved by the United States Food and Drug Administration. [7][8][9][10] Initial clinical results have been promising, where postoperative refractive outcomes were comparable to standard LASIK with few complications. 11,12 However, more studies are needed to assess the safety and efficacy of this new surgical procedure.…”
mentioning
confidence: 93%
“…10 After application of topical anesthesia, standard sterile draping and insertion of the speculum, the patient's eye was centered and docked with the curved interface cone before application of suction fixation. The laser treatment started with the posterior surface of the refractive lenticule (spiral in) before the lenticule border was created.…”
Section: A Prospective Clinical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…ingrowth and monocular ghost images. 10,11,19 Recently, we found irregular postoperative topography in 18 of 1,574 eyes, giving rise to ghost images in six cases. 23 Topography-guided PRK was performed in four of these eyes, ameliorating the symptoms in three cases.…”
Section: Safetymentioning
confidence: 97%
“…In the first clinical studies, ReLEx flex was reported to have delayed visual recovery in comparison with FS-LASIK [11,27]. However, later studies suggested that the laser scanning pattern and energy had an impact on the lenticule surface quality and the immediate postoperative outcome [28 • , 29, 30].…”
Section: Visual Outcomementioning
confidence: 99%